A Literature Survey on Security & Privacy Issues in IoT - Kaur, Kamaljit; Kaur, Ramanjot (International Journal of Computer Sciences and Engineering, 2021)
In the 21st century IoT plays a major role in all domains The Internet of Things (IoT) is the network of billions of devices, people and services to Interconnect and exchange information and useful data. The IoT applications are highly affirming to increase the level of comfort, efficiency and automations for the user. Due to rapid increase of devices, people, vehicles connecting with the IoT network from anywhere and anytime which causes security and privacy issues.The high level of security and privacy, authentication and recovery from the attacks is required to implement an IoT automated world. All the IoT security threats including DoS, Man-in-the-middle, Tempering, jamming etc. are discussed in the survey.